APPLICATION OF INFORMATION TECHNOLOGIES IN INFECTIOUS DISEASES: A MODERN APPROACH (Modern education and development, 2025)
Advancements in information technologies (IT) have significantly transformed the field of medicine, offering innovative solutions to improve patient outcomes, streamline processes, and enhance research capabilities. This article focuses on the application of IT in managing infectious diseases, emphasizing the importance of data analytics, telemedicine, and digital platforms for disease surveillance and control.